White Dendrimer Organic Light Emitting Diodes: Exciton Formation and Transfer. Issue 24 (25th October 2020) - von Reventlow, Lorenz Graf; Jiang, Wei; Stoltzfus, Dani M.; Russell, Steven M.; Burn, Paul L.; Colsmann, Alexander
Abstract: In this work solution‐processed organic white‐light emitting diodes comprising a blend of red and blue phosphorescent dendrimers are presented. In contrast to common small molecule blended‐dye organic light emitting diodes (OLEDs), the bulky dendrons between the light emitting moieties increase the spacing and hamper the transfer of excitons between the dyes. The reduced transfer of the excitons from the blue dye to the red dye enables greater control over OLED color avoiding the issue in which small variations in the concentration of the red dye can dramatically change the emission color. Thus, the approach leads to enhanced manufacturing reproducibility. Transient electroluminescence measurements provide detailed insights into the charge carrier and exciton formation and transfer dynamics within the device. Abstract : Blue and red dendrimer emitters in blended‐dye organic light emitting diodes (OLEDs) lead to a reduction of energy transfer from the blue to the red dye. As a consequence, higher amounts of red dye can be used, resulting in a reduced concentration sensitivity of the color and a more reproducible manufacturability. Exciton generation, exciton transfer, and charge carrier trapping are investigated via transient electroluminescence.